Hva er praktisk teologi? (Nordic Journal of Practical Theology, 2020)
What is practical theology? With Olav Skjevesland’s 1999 volume on practical theology in the Norwegian and Nordic context as a backdrop and Bonnie J. Miller-McLemore’s fourfold understanding of practical theology as its point of departure, this article seeks to sketch out some perspectives of the international field of practical theology. We thus begin by presenting and discussing practical theology as (1) a discipline, (2) a curricular area and an umbrella term for sub disciplines such as homiletics, pastoral care, liturgical studies, etc., (3) a method, or more precisely methods, and (4) a way of life. Following this presentation, the article argues for an understanding of practical theology where practice and theory, and the practices of research and teaching are enacted in a mutually enriching and engaging way and, thus, moves beyond a «binary captivity» between the clerical and academic paradigm. Emphasizing an empirical and hermeneutical approach to practical theology, typical for the field the way it is being undertaken in our Nordic context, we make the case that such research contributes to the field of practical theology, including the practical theological sub- disciplines, not by having access to a particular theological epistemology but by allowing and inviting new theological voices and perspectives into the theological conversation, and, hence, to the production of novel theological knowledge.